Risk Factors of Premature Coronary Artery Disease - Mujaddid Mudassir, Javed Iqbal, Muhammad Shafique Arshad, Ali Raza, Qudsia Anjum Qureshi, Mujaddid Mudassir, Javed Iqbal, Muhammad Shafique Arshad, Ali Raza, Qudsia Anjum Qureshi (Journal of Rawalpindi Medical College, 2021)
Introduction: Coronary artery disease (CAD) is one of the commonest and leading causes of death throughout the world. It is becoming common in the younger age group as well. This study was carried out to analyze the risk factors present in young patients who presented with acute Myocardial Infarction (M.I). Materials and Methods: In this descriptive cross-sectional study, we included 120 patients of age 20-35 years of age who presented with the first episode of acute M.I. Study was conducted at Pakistan Institute Of Medical Sciences, Islamabad, department of cardiology for all patients with first MI from 1st February 2016 to 31st January 2018. Twelve risk factors were studied including Gender, Hypertension, Diabetes mellitus, dyslipidemia, sedentary lifestyle, family history of premature CAD, obesity, smoking, dietary habits, profession, socioeconomic stress, drug addictions. The frequency of risk factors was calculated. Results: Results showed that some of the risk factors were present in higher proportion e.g. smoking, sedentary lifestyle, poor dietary habits, and stressful socioeconomic conditions. Most of the patients in the younger age group were drivers. The results of our study showed that male patients were higher(93.3%) in proportion to female patients (6.7%). 33% of patients were drivers, 13% plumbers, 13% shopkeepers, 10% businessmen, 8% laborers, 5% policemen, 5% students, 5% bank officers, 3% engineers, 2% teachers, 1% doctors. 68.3% of patients were smokers. 58.3% of patients were having high-stress scores. 23.3% of patients were having moderate stress score.18.3% were having a low-stress score. 56% of patients were having dyslipidemia.48% of patients were obese. Family history was present in 26.7% of patients. Conclusion: For patients presenting with premature CAD, Some of the modifiable risk factors include hypertension, sedentary lifestyle, fatty dietary habits, obesity, smoking, diabetes, dyslipidemia. The profession also affects the development of IHD as is evident from our study. So primary preventive strategies need to be implied to prevent the development of IHD, especially in individuals who are at risk.